Using Click-Chemistry for Visualizing in Situ Changes of Translational Activity in Planktonic Marine Bacteria - Leizeaga, Ainara; Estrany, Margarita; Forn, Irene; Sebastián, Marta (Frontiers in Microbiology, 2017)
A major challenge in microbial ecology is linking diversity and function to determine which microbes are actively contributing to processes occurring in situ. Bioorthogonal noncanonical amino acid tagging (BONCAT) is a promising technique for detecting and quantifying translationally active bacteria in the environment. This technique consists of incubating a bacterial sample with an analog of methionine and using click-chemistry to identify the cells that have incorporated the substrate. Here we established an optimized protocol for the visualization of protein-synthesizing cells in oligotrophic waters that can be coupled with taxonomic identification using Catalyzed Reporter Deposition Fluorescent in situ Hybridization (CARDFISH). We also evaluated the use of this technique to track shifts in translational activity by comparing it with leucine incorporation, and used it to monitor temporal changes in both cultures and natural samples. Finally, we determined the optimal concentration and incubation time for substrate incorporation during BONCAT incubations at an oligotrophic site. Our results demonstrate that BONCAT is a fast and powerful semi-quantitative approach to explore the physiological status of marine bacteria.